A new species of Lindernia (Linderniaceae) from Tanzania - Fischer, Eberhard; Vollesen, Kaj B.; Darbyshire, Iain (Phytotaxa, 2023)
The new species Lindernia sallyae from Tanzania, Mpanda District is described and illustrated. It differs from Lindernia linearifolia and L. monroi in the lack of basal rosulate leaves, the taller habit, the calyx with shorter tube and the acute lobes, the yellow corolla with purple marks and veins, the larger lower lip of the corolla, the longer abaxial stamens with acute anthers, and the glabrous adaxial stamens. The ecology of this probably poikilohydric species is briefly discussed. The endemic flora of the Uzondo Plateau, the type locality for this new Lindernia species, is highlighted.